Peningkatan Pemahaman Tentang Perilaku Konsumen Pada UMKM Buket Bunga Betterstore Samarinda - Auliya Syafira; Meilynda Satriani; Aura Nuzulul Rahmah; Muhammad Suyudi; Angga Kusumah (PT Ininnawa Paramacitra Edu, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the local economy, yet many business owners still find it difficult to understand their consumers' behavior. This community service activity was carried out at Betterstore, an artificial flower bouquet business in Samarinda, with the goal of helping the owner and staff better understand consumer behavior, including purchasing habits, customer preferences, and the concept of consumer satisfaction. The activity was conducted through direct interviews and face -to-face educational sessions with Betterstore's owner and staff. As a result, the business owner gained a cl earer understanding of customer purchasing patterns, the importance of identifying the right target market, and the need to keep up with product trends on social media. Throughout the activity, Betterstore's team was enthusiastic and open, and expressed their commitment to applying these insights in their marketing and product development going forward. This activity is hoped to support Betterstore's growth and competitiveness within Samarinda's growing creative industry.